Pengoptimalan Pembangkit Listrik Tenaga Surya Di Terminal Purabaya - Setiawan, Ongky Adi; Prabowo, Yuliyanto Agung; Munir, Misbahul; Mirando, Sefian Yordanius (Institut Teknologi Adhi Tama Surabaya, 2025)
Indonesia's strategic location along the equator provides a significant potential for harnessing solar energy. This research explores the utilization of solar energy to reduce high electricity operating costs at Purabaya Terminal. It aims to design and evaluate a solar power plant (PLTS) system for the terminal, employing two maximum power point tracking (MPPT) methods: Perturb Observe (PO) and Hill Climbing. The study utilizes three months of power consumption data from Purabaya Terminal, alongside solar irradiation and temperature data sourced from the Meteorology, Climatology, and Geophysics Agency (BMKG) in Surabaya. The research methodology involves data collection, simulation using MATLAB software, and a comparative analysis of the two MPPT methods. The findings of this study offer actionable recommendations for reducing electricity costs at Purabaya Terminal and provide a reference framework for designing PLTS systems at other locations. In conclusion, the PO method demonstrated greater efficiency and closely matched the load demand of 110,123 Watts.